Evaluate the effectiveness of the Storynomics Model in preserving and promoting the cultural heritage of Sumbawa City in Indonesia - PATTARAY, Anas (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to find a model of cultural heritage development with a collaborative approach between cultural heritage and storynomics of sustainable tourism in Heritage City. Tourism potential of Sumbawa City's cultural heritage as a cultural heritage of the past with historical value, tourist attraction, and conservation-based tourism destinations that impact improving local community's economy. The research uses a descriptive, explanatory approach to cultural heritage objects. Data collection is obtained from informants as primary data to explore information about Sumbawa. In addition, data was obtained from the distribution of questionnaires to assess the physical condition of buildings and tourism performance and past literature documentation of Sumbawa. The results of this study provide an overview of the historical tourism of Sumbawa City, which presents the authenticity of the past as a sustainable historical tourist attraction. The review was conducted with social interaction theory with an analysis of the relationship between past events, traces of the history, local community culture, and historical sources that are the tourist attractions.